Two mechanisms of stratospheric ozone loss in the Northern Hemisphere, studied using data assimilation of Odin/SMR atmospheric observations - K. Sagi; K. Pérot; D. Murtagh; Y. Orsolini (Atmospheric Chemistry and Physics, 2017)
Observations from the Odin/Sub-Millimetre Radiometer (SMR) instrument have been assimilated into the DIAMOND model (Dynamic Isentropic Assimilation Model for OdiN Data), in order to estimate the chemical ozone (O 3 ) loss in the stratosphere. This data assimilation technique is described in Sagi and Murtagh (2016), in which it was used to study the inter-annual variability in ozone depletion during the entire Odin operational time and in both hemispheres. Our study focuses on the Arctic region, where two O 3 destruction mechanisms play an important role, involving halogen and nitrogen chemical families (i.e. NO x = NO and NO 2 ), respectively. The temporal evolution and geographical distribution of O 3 loss in the low and middle stratosphere have been investigated between 2002 and 2013. For the first time, this has been done based on the study of a series of winter–spring seasons over more than a decade, spanning very different dynamical conditions. The chemical mechanisms involved in O 3 depletion are very sensitive to thermal conditions and dynamical activity, which are extremely variable in the Arctic stratosphere. We have focused our analysis on particularly cold and warm winters, in order to study the influence this has on ozone loss. The winter 2010/11 is considered as an example for cold conditions. This case, which has been the subject of many studies, was characterised by a very stable vortex associated with particularly low temperatures, which led to an important halogen-induced O 3 loss occurring inside the vortex in the lower stratosphere. We found a loss of 2.1 ppmv at an altitude of 450 K in the end of March 2011, which corresponds to the largest ozone depletion in the Northern Hemisphere observed during the last decade. This result is consistent with other studies. A similar situation was observed during the winters 2004/05 and 2007/08, although the amplitude of the O 3 destruction was lower. To study the opposite situation, corresponding to a warm and unstable winter in the stratosphere, we ...